X—ray photoelectron spectroscopy study on adsorption property of harmful air pollutants on zeolite prepared from fly ash. (25th July 2018) - Siddharth,; Maiti, S; Raj, H; Bisht, R S; Minocha, A K; Panigrahi, S K; Alexander, S; Sameer,; Singh, M
Abstract: The present study focuses on the adsorption property of zeolite material prepared from fly ash for NOx, CO and other harmful air pollutants. X-ray diffraction (XRD) pattern of zeolite shows formation of two phase namely, Analcime and Na-P1 (Na6 Al6 Si10 O32 . 12 H2 O). X-ray photoelectron spectroscopy (XPS) study reveals the adsorption of NO2, NO, N2 O and CO pollutants on zeolite which are confirmed by core level XPS spectra of N 1s, O 1s and C 1s peaks. The two-zeolite phases have low silica content having acidic and thermal resistivity properties. These properties can be exploited in internal as well as external building environment for adsorption of harmful air pollutants.